Streptanthus purpureus sp. nova (Cruciferae), an endemic nickel hyperaccumulator from Sierra Nevada (California, USA) - Sánchez-Mata, Daniel; de la Fuente, Vicenta; Rufo, Lourdes; Rodríguez, Nuria; Amils, Ricardo (Lazaroa, 2013)
Abstract: Sánchez-Mata, D., de la Fuente, V., Rufo, L., Rodríguez, N. & Amils, R. Streptanthus purpureus sp. nova (Cruciferae), an endemic nickel hyperaccumulator from Sierra Nevada (California, USA). Lazaroa 34: (2013). The genus Streptanthus Nutt. (Cruciferae) is one of the most important indicators of ultramafic floras in Western North America. This genus contains taxa that are endemic or tolerant of ultramafic soils. One of these taxa, Streptanthus polygaloides sensu lato (s.l.) are annual nickel hyperaccumulators strictly confined to ultramafic soils throughout the Californian Sierra Nevada foothills. Some clarifications are discussed regarding the taxonomy and ecology of this complex, leading to the recognition of a new taxon: Streptanthus purpureus sp. nova